Clinical results of 40 years of paediatric keratoplasty in a single university eye clinic. (23rd July 2013) - Hovlykke, Maria; Hjortdal, Jesper; Ehlers, Niels; Nielsen, Kim
Abstract. Purpose: To evaluate indications for paediatric keratoplasty in recipients aged ≤16 years and assess long‐term clinical outcome. Method: Recipients were identified from records of the Danish Cornea Bank. Data were collected from patient journals, clinical follow‐up examinations and questionnaires and stratified into pre‐, peri‐ and postoperative variables. Diagnoses were classified into acquired traumatic, acquired nontraumatic and congenital groups. Recipients were divided into groups of <8 and ≥8 years. Data were analyzed using relative percentages and Kaplan–Meier survival plots. Results: Thirty‐three out of sixty identified recipients (73 keratoplasties in 63 eyes) were invited. Twenty‐four accepted, seven still attended follow‐up in our clinic. Follow‐up data reached 95% of the eligible recipients (median follow‐up 11 years). Twenty‐three per cent were <8 years and 77%≤8 years. Diagnoses were mainly acquired nontraumatic (69%), acquired traumatic (12%) and congenital (7%). Indications were primarily optical (52%) or tectonic (41%). Graft survival was best in the acquired nontraumatic group (except regrafts) (median survival 15–20 years) and poorest in the regraft subgroup as well as the acquired traumatic and congenital groups (median survival 1–2 years). Graft failure was higher in the youngest with predisposing risk factors and in combined procedures. In terms of indications, visual improvement and eye preservation was achieved in 70%. Conclusion: Paediatric keratoplasty was successful regarding indication. Graft survival was best in the acquired nontraumatic group and poorest in the congenital group. Vascularization and/or combined risk factors, additional surgeries and young recipient age influenced negatively on graft survival.